Dual inhibition of thrombin and activated factor X attenuates disseminated intravascular coagulation and protects organ function in a baboon model of severe Gram-negative sepsis - Schöchl, Herbert (Crit Care, 2017)
BACKGROUND: Inhibition of procoagulant pathways may improve outcome in sepsis. We examined whether a dual short-acting thrombin (factor II) and factor X (FX)a inhibitor (SATI) ameliorates sepsis-induced disseminated intravascular coagulation (DIC) and is organ-protective. METHODS: Escherichia coli were infused for 2 h in 22 anesthetized baboons. The control (CO) group (n = 8) received sterile isotonic solution only. In the treatment groups, SATI was administered starting 15 minutes after the end of the bacterial exposure. In the low-dose group (LD-SATI, n = 8), SATI was infused with 75 μg/kg/h for the first hour, followed by 23 μg/kg/h until the end of the study. In the high-dose SATI group (HD-SATI, n = 6), 225 μg/kg/h was administered for the first hour followed by continuous infusion of 69 μg/kg/h until termination of the study. RESULTS: Sepsis-induced DIC was attenuated, as reflected by lower peak thrombin-antithrombin complexes (threefold) and D-dimer levels (twofold) in both SATI groups compared to the CO. This coincided with strongly improved cell/organ protection assessed by decreased levels of lactate dehydrogenase (threefold), creatinine (twofold), aspartate aminotransferase (threefold), and amylase (twofold) compared to the CO group. Anuria, which started at 8 h in the CO group, was prevented in both SATI groups. Peak interleukin-6 release at 12 h was prevented in the treatment groups. In both SATI groups, fewer catecholamines were necessary and no bleeding complications were observed. CONCLUSIONS: Dual inhibition of thrombin and FXa preserved activation of coagulation, protected organ function and ameliorated inflammation in severe Gram-negative sepsis in baboons. SATI could be a novel therapeutic agent against sepsis-induced DIC.